Historical data of geoelectric field observations in Japan. Issue 1 (11th December 2021) - Nagamachi, Shingo; Arita, Shin; Hirota, Eiji
Abstract: The Kakioka Magnetic Observatory (KMO) of the Japan Meteorological Agency (JMA) made geoelectric field observations at Kakioka, Memambetsu and Kanoya from 1932, 1949 and 1948, respectively, until February 2021, when observations at all three sites were terminated. The digital numerical data are available on the KMO website, although not all observation periods are covered. In this article, we introduce the available datasets and summarize the metadata regarding the observations, such as the electrodes, recording system, maintenance methods and data processing. Abstract : The Kakioka Magnetic Observatory (KMO) of the Japan Meteorological Agency (JMA) made geoelectric field observations at Kakioka, Memambetsu and Kanoya from 1932, 1949 and 1948, respectively, until February 2021, when observations at all three sites were terminated. These long‐term fixed‐site observations over a period of more than 70 years are unique and have contributed to the investigation of seismic electromagnetic phenomena and space weather phenomena.